1997
DOI: 10.1523/jneurosci.17-22-08804.1997
|View full text |Cite
|
Sign up to set email alerts
|

Excitotoxicity in the Enteric Nervous System

Abstract: Glutamate, the major excitatory neurotransmitter in the CNS, is also an excitatory neurotransmitter in the enteric nervous system (ENS). We tested the hypothesis that excessive exposure to glutamate, or related agonists, produces neurotoxicity in enteric neurons. Prolonged stimulation of enteric ganglia by glutamate caused necrosis and apoptosis in enteric neurons. Acute and delayed cell deaths were observed. Glutamate neurotoxicity was mimicked by NMDA and blocked by the NMDA antagonist D-2-amino-5-phosphonop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(56 citation statements)
references
References 46 publications
3
50
2
Order By: Relevance
“…Glutamate release and NMDA receptor activation induces nitric oxide, and other free radicals that cause tissue injury [31] . Glutamate release during I/R could also cause toxicity in the enteric nervous system, which could cause motility alterations [32] . One recent study found that intestinal I/R causes myenteric plexus ganglion cell reduction and death [33] .…”
Section: Issnmentioning
confidence: 99%
“…Glutamate release and NMDA receptor activation induces nitric oxide, and other free radicals that cause tissue injury [31] . Glutamate release during I/R could also cause toxicity in the enteric nervous system, which could cause motility alterations [32] . One recent study found that intestinal I/R causes myenteric plexus ganglion cell reduction and death [33] .…”
Section: Issnmentioning
confidence: 99%
“…Indeed, cell death of ENS precursors is seen in the esophagus of Ret -/- (Taraviras et al, 1999) and Phox2b -/-mice (Pattyn et al, 1999), and in the mesenchyme surrounding the neural tube in Sox10 Dom /Sox10 Dom mice (Kapur, 1999;Southard-Smith et al, 1998). In addition, adult guinea pig enteric neurons undergo apoptosis in response to glutamate (Kirchgessner et al, 1997), and trkC-expressing rat ENS precursors undergo apoptosis in response to NT3 withdrawal (Chalazonitis et al, 2001). Thus, despite demonstrable trophic factor dependence, the absence of identifiable cell death in wild-type mice suggests that during normal development ENS precursors receive an adequate amount of trophic factor for survival.…”
Section: Trophic Factors and The Ensmentioning
confidence: 99%
“…Glutamate may bind to glutamate receptors, for example NMDA, AMPA, and metabotropic glutamate receptors, which have been described on submucosal and myenteric neurons of the intestine as well as on vagal afferents (Giaroni et al 2003;Kirchgessner 2001;Kirchgessner et al 1997;Liu et al 1997;McRoberts et al 2001;Tong and Kirchgessner 2003;Wiley et al 1991). These glutamate receptors might have multiple effects on modulation of motor and secretory functions (Cosentino et al 1995;Rhoads et al 1995;Sinsky and Donnerer 1998;Wiley et al 1991).…”
Section: Functional Considerationsmentioning
confidence: 99%